A igualdade como paradigma para efetivação de um direito processual coletivo no Brasil - Camacho, Henrique [UNESP] (2014)
The scope of this dissertation is demonstrating the relation between equality and collective protection, aiming to prove the salutary integration of procedural mechanisms to defend collective rights, in a wide approach, and the fundamental rights. The theme is multidisciplinary, and involves some fields of juridical science, like State theory and Constitutional Law, and also the legal instruments that discipline the national collective judicial procedure. It's intended to seek integration between the creation of societies and the structure of the so called Democratic State of Law with the instruments that allow the ones under jurisdiction to fight for effective fundamental rights and public policies. Equality, in this research, is conceptualized as a paradigm, once it makes part of a structure that integrates paradoxes, resulting of relations and conflicts between existing norms to protect fundamental rights. However, the traditional debates about equality as a rule or principle aren't ignored; in fact, they aren't considered the best solution to the issues of modern society, result of a historical process with residuals located in an unequal, globalized and individualist society. Matching subjects compose the theme intended in the research, such as the comparison between equality and Justice, the conceptualization and comprehension of democracy, and the analysis of some cases taken from superior courts to illustrate integration between the norm (either collective protection or Constitutional norm supporting fundamental rights) and reality. This way, it's possible to insert the research in a relevant level for juridical science, not for being unique or a reference, but for worrying about presenting equality under a new perspective, inciting debates. The structure of the research sought an essentially dogmatic juridical methodology, maintaining, however, an analytical dimension as its main axle, without ignoring the utilization of another...